Changes in the treatment strategy following intracoronary pressure wire in a contemporaneous real-life cohort of patients with intermediate coronary stenosis. Results from a nationwide registry. (3rd October 2022) - Rodriguez Leor, O; Toledano, B; Lopez Palop, R; Rivero, F; Brugaletta, S; Linares, J A; Puigfel, M; Sadaba, M; Vaquerizo, B; Rondan, J; Gomez, I; Saez, R; et al.
Abstract: Background: Intracoronary pressure wire is useful to guide revascularization in patients with coronary artery disease. Aims: To evaluate changes in diagnosis (coronary artery disease extent), treatment strategy and clinical results after intracoronary pressure wire study in real-life patients with intermediate coronary artery stenosis. Methods: Observational, prospective and multicenter registry of patients in whom pressure wire was performed. The extent of coronary artery disease and the treatment strategy based on clinical and angiographic criteria were recorded before and after intracoronary pressure wire guidance. 12-month incidence of MACE (cardiovascular death, non-fatal myocardial infarction or new revascularization of the target lesion) was assessed. Results: 1414 patients with 1781 lesions were included. Complications related to the procedure were reported in 42 patients (3.0%). The extent of coronary artery disease changed in 771 patients (54.5%). Figure 1 shows extent of coronary artery disease based on coronary angiographic analysis and following intracoronary pressure wire study. Figure 2A shows the extent of coronary artery disease based on coronary angiographic analysis and its reclassification following intracoronary pressure wire study. Figure 2B shows the extent of coronary artery disease following pressure wire study and its classification when only considering the coronary angiographic analysis. Figure 2 shows change in treatment strategy following intracoronary pressure wire study. There was a change in treatment strategy in 779 patients (55.1%) (18.0% if medical treatment; 68.8% if PCI; 58.9% if surgery (p<0.001 for PCI vs medical treatment; p=0.041 for PCI vs CABG; p<0.001 for medical treatment vs CABG). In patients with PCI as the initial strategy, the change in strategy was associated with a lower rate of MACE (4.6% vs 8.2%, p=0.034). Conclusions: The use of intracoronary pressure wire was safe and led to the reclassification of the extent of coronary disease and change in the treatment strategy in more than half of the cases, especially in patients with PCI as initial treatment. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): The registry was endorsed by the Intracoronary Diagnostic Techniques Working Group of the Interventional Cardiology Association of the Spanish Society of Cardiology. The study was supported by an unconditional grant from Philips-Volcano, Abbott Vascular, and Boston Scientific. The sponsors did not have access to the database or the final results until the preparation of this abstract. None of them participated in the preparation or review of this abstract.